Pengaruh Literasi Keuangan, Gaya Hidup, E-Money terhadap Perilaku Konsumtif Generasi Millenial dengan Kontrol Diri Sebagai Moderasi - Marcellino Dwi Rahmanda Agasi; Dwi Nita Aryani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The purpose of this study are to examine the effect of financial literacy, lifestyle, E-Money on Millennial Generation Consumptive Behavior in Blitar City with self-control as moderation. The sample used in this research consisted of 418 respondents. Respondents taken from BPS Blitar City data were Millennial Generation Respondents. This research uses quantitative research with SPSS as the test tool. The results of the t test between X1 and Y show t = -0.842 > 1.648, so the influence of X1 (financial literacy) is not significant. the results of the t test between X2 and Y show t count = 2.607 > 1.648, so the influence of X2, (lifestyle), has a significant effect on consumptive behavior so hypothesis 2 is accepted. The results of the t test between X3 and Y shows t count = 9.910 > 1.648, so the influence of X3 (E-money) has a significant effect on Consumptive Behavior (Y). The result of t count = 2.835 > 1.648 then the influence of X1 with moderation of self control (Z) has a significant effect on consumptive behavior (Y) so that hypothesis 4 is accepted. The t count = 0.870, less than t table, hence the lifestyle moderated by self-control has no significant effect on consumptive behavior. The results of the t test, namely t count = -0.486, less than t table, namely 1.648, so E-Money, which is moderated by self-control, has no significant effect on consumptive behavior. Keywords: Financial Literacy; E-money; Life Style; Consumptive Behaviour; Millennial